Ternary hybrid PtM@polyaniline (M = Ni, FeNi) counter electrodes for dye-sensitized solar cells. (20th November 2018) - Wang, Yudi; Duan, Jialong; Zhao, Yuanyuan; Yang, Xiya; Tang, Qunwei
Abstract: Developing efficient and cost-effective counter electrodes (CEs) to catalyze triiodide reduction reaction is a persistent objective for high-performance dye-sensitized solar cells (DSSCs). One promising solution is to design electron-enriched electrode materials by combining conductive polymers with alloys. In this work, ternary hybrid PtM@polyaniline (M = Ni, FeNi) CEs are synthesized by one-step replacement reaction and in-situ polymerization reaction. When assembling into liquid-junction DSSCs, the power conversion efficiencies of 8.52% and 8.39% for the devices tailored with PtNi@polyaniline and PtFeNi@polyaniline CEs can be obtained. The experimental results demonstrate that the enhanced photovoltaic performances are mainly attributed to matching work function and high electrocatalytic activity of these well-designed hybrid CEs. Arising from the competitive reactions between transition metal and I2 /I3 − species, the dissolution reaction of Pt in liquid electrolyte is restricted and therefore the long-term stability of corresponding devices are significantly enhanced. Graphical abstract: Highlights: Ternary hybrid PtM@PANi CEs are prepared by one-step method. Ternary hybrid PtM@PANi CEs are used for DSSC applications. The hybrid CEs present matching work functions and enhanced catalytic activities. The device yields a maximized PCE of 8.52% under one sun illumination.